ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI KELAPA SAWIT DI DESA BANGUN HARJA: ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI KELAPA SAWIT DI DESA BANGUN HARJA - Fadilah, Nor; Suroto, Suroto (Politeknik Seruyan, 2025)
The income of oil palm farmers in Bangun Harja Village shows significant variation despite the cultivation of the same commodity. One of the primary issues to investigate is the fluctuation in the price of Fresh Fruit Bunches (FFB), which can directly impact farmers' income. Additionally, land quality and the application of cultivation techniques play crucial roles in determining harvest outcomes and income. Access to agricultural inputs such as fertilizers and equipment, along with socio-economic factors, government policies, and supply chain issues, are other challenges that need consideration. A comprehensive understanding of these factors will provide deeper insights into the dynamics of oil palm farmers' income in the village. The objectives of this study are: to analyze the impact of price on oil palm farmers' income in Bangun Harja Village; to examine the influence of production costs on income; to assess the effect of land area on income; and to evaluate the simultaneous effects of price, production costs, and land area on income. The study utilizes validity and reliability tests of the data, multiple linear regression analysis, F-test (ANOVA), and coefficient of determination tests. Conducted in Bangun Harja Village with 17 sample data points, the research employs secondary and primary data collected through questionnaires, which are then tested for validity and reliability. Multiple linear regression analysis using SPSS version 26.0 reveals that price (X1) has a significant effect on income (Y) with a t-value of 0.629 and a significance level of 0.533. Production costs (X2) significantly impact income with a significance level of 0.775 and 0.533. Land area (X3) does not have a significant effect on income with a t-value of -4.291 and a significance level of 0.05. Simultaneously, price, production costs, and land area (X1, X2, and X3) collectively affect income with a t-value of 7.617 and an R-squared value of 0.637, indicating that these variables contribute 63.7% to the income of oil palm farmers in Bangun Harja Village. Keywords: Palm Oil, Income, Price, Production Costs, Land Area